Plugin the X value from the first equation into the second one:
3(2y+4) = 4-2y -- Now solve for Y
6y +12 = 4-2y
8y = -8
y = -1 -- Plugin the Y value into one of the equations to find X
x = 2(-1)+4
x = 2
2007-05-13 09:51:55
·
answer #1
·
answered by nimble_rabit 1
·
0⤊
0⤋
x=2y+4 2y = x - 4
3x = 4-2y 2y = 4 - 3x
then x - 4 = 4 -3x
x + 3 x = 4 + 4
4 x = 8
x = 2
where 2 y = x - 4
2y = 2 - 4
2 y = -2
y = -1
x= 2 , y = -1 s.s ={ ( 2 , -1 ) }
2007-05-13 10:01:14
·
answer #2
·
answered by muhamed a 4
·
0⤊
0⤋
There are lots of ways to do this. Here's one.
Multiply the first equation through by 3:
3x = 6y + 12
Then subtract the second equation from the new first equation:
3x = 6y + 12
-[3x = 4 - 2y]
=> 0 = 8y +8
Now divide both sides by 8 to get
0 = y + 1
Subtracting 1 from both sides gives
y = -1
Now plug this back into either of the original equations to solve for x. The first one is easier:
x = 2*(-1) + 4
so x = 2
The solution is x = 2, y = -1
You can check this in the second equation just to be sure:
3 * 2 = 4 - 2* (-1)
6 = 6, so it's right!
2007-05-13 09:54:33
·
answer #3
·
answered by Eve D 3
·
0⤊
0⤋
x=2y+4 (equation 1)
3x=4-2y (equation 2)
So substitute equation 1 into equation 2, i.e. wherever you see 'x' in equation 2, replace it with '2y+4'
So we have:
3(2y+4) = 4 - 2y
6y + 12 = 4 - 2y
subtract 12 from both sides:
6y + 12 - 12 = 4 - 2y - 12
6y = -8 - 2y
Add 2y to both sides:
6y + 2y = -8 - 2y + 2y
8y = -8
Divide both sides by 1:
y = -1
So now subsitute y=-1 into equation 1 to find x:
x=2y+4
x=(2*-1) +4
x = -2+4
x=2
So the answer is: x=2, y=-1
2007-05-13 09:54:14
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
3(2y+4) = 4-2y
8y +8 = 0
y = -1
x = -2+4 = 2
2007-05-13 09:52:12
·
answer #5
·
answered by bz2hcy 3
·
0⤊
0⤋
Adding gives:-
4x = 8
x = 2
2 = 2y + 4
2y = - 2
y = - 1
Solution is x = 2, y = - 1
2007-05-13 10:04:49
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
x-4=2y 2y=4-3x
x-4=4-3x
x=8-3x
4x=8
x=2 2y=4-(3*2)
2y=4-6
2y=-2
y=-1
therefore x=2 and y=-1
2007-05-13 10:48:10
·
answer #7
·
answered by books_are_heaven 2
·
0⤊
0⤋
X=2Y+4
3(2Y+4)=4-2Y
X=2Y+4
6Y+12=4-2Y
X=2Y+4
8Y=-8
X=2Y+4
Y=-1
X=2(-1)+4
Y=-1
X=2
Y=-1
2007-05-13 10:08:01
·
answer #8
·
answered by yoseff 1
·
0⤊
0⤋